REKONTRUKSI METODOLOGI HUKUM ISLAM KONTEMPORER - Materan, Materan (Mazahib, 2012)
This paper aims to explore ways of view (weltanshaung) Al-Quran for the establishment of Islamic law, the ethical principles of the Qur'an in the form of universalism, justice, equality, and general welfare of the contextual and contemporary. It is important to remember that Islamic law is the most fundamental part in creating public improvements in accordance with the times and places, both in aspects of family law, economics, criminal, female (gender), medical, technological, political and even religious aspects. Therefore, the reconstruction methodology of Islamic law is an absolute, so that the application of Islamic law itself does not ignore the ethical principles of the Al-Qur’an.